The Use of Active Filter to Mitigate Harmonics in Cryptocurrency Mining Computer - Rendika, Damai Lendra Boy; Suherman; Hasan, Syafruddin (Jurnal Sistem Teknik Industri, 2025)
Cryptocurrency mining computers act as non-linear loads, introducing significant harmonic distortions that degrade power quality and system efficiency. This study explores the use of a shunt active filter with an inductance of 0.0075 H to reduce harmonics in a high-load cryptocurrency mining rig. Harmonic measurements were collected using a Fluke 43 Power Quality Analyzer and validated through MATLAB/Simulink simulations. Results revealed a substantial reduction in Total Harmonic Distortion in Current (THDi) from 76.62% to 9.18%, achieving compliance with IEEE 519-2014 standards. Additionally, major harmonic orders—specifically the 3rd, 5th, and 7th—were each suppressed by more than 90%. The system’s power factor improved markedly from 0.85 to 0.99, indicating enhanced energy efficiency. These outcomes demonstrate the effectiveness of active filters in improving power quality in cryptocurrency mining operations and suggest their practical application in industrial-scale setups to minimize energy losses, extend hardware lifespan, and support grid stability.